Effects of group music sessions on cognitive and psychological functions in healthy older adults - Shinada, Takamitsu; Takahashi, Michio; Uno, Akari; Soga, Keishi; Taki, Yasuyuki (Frontiers in Aging, 2025)
IntroductionWith the rapid aging of the population worldwide and the prevalence of dementia and mental health problems among older adults, it is important to extend healthy life expectancy by maintaining brain and mental health. Playing musical instruments, which requires the integration of auditory, visual, and somatosensory functions, is considered an effective way to prevent the development of dementia. However, the effectiveness of group (band) music sessions in healthy older adults has not been investigated. Our purpose, therefore, was to investigate the effects of group music sessions on cognitive and psychological functions among healthy older adults.MethodsIn this open-label randomized controlled trial, participants aged 65–74, who had no musical experience, were randomly assigned to either the intervention or control group. The intervention group received in weekly 90-minute sessions with the instrument for 16 weeks. The control group received no intervention.ResultsThe results showed that the Mini-Mental State Examination (MMSE) total score and the Wechsler Memory Scale Logical Memory Ⅱ (WMS-LM Ⅱ) score improved significantly, and the Vigor–Activity subscale score of the Profile of Mood States 2nd Edition (POMS 2) tended to improve.DiscussionThese findings indicated that group music sessions have a potentially beneficial effect for maintaining and improving cognitive and psychological functions in healthy older adults.